Brucellosis in pregnant women from Pakistan: an observational study. Issue 1 (December 2016) - Ali, Shahzad; Akhter, Shamim; Neubauer, Heinrich; Scherag, André; Kesselmeier, Miriam; Melzer, Falk; Khan, Iahtasham; El-Adawy, Hosny; Azam, Asima; Qadeer, Saima; Ali, Qurban
Abstract Background Brucella species occasionally cause spontaneous human abortion. Brucella can be transmitted commonly through the ingestion of raw milk or milk products. The objective of this study was to determine the sero-prevalence of and to identify potential risk factors for brucellosis in pregnant women from Rawalpindi, Pakistan. Methods We conducted a cross-sectional study at the Gynecology Outdoor Patient department of the Benazir Bhutto Hospital, Rawalpindi, Pakistan from March to June 2013. Data related to potential risk factors and clinical history was collected by individual interviews on the blood sampling day. The 429 serum samples collected were initially screened by Rose Bengal Plate Agglutination test for the detection ofBrucella antibodies. We applied standard descriptive statistics and logistic regression analyses. Results Twenty five (5.8 %; 95 % confidence interval (CI): 3.8 % -8.5 %) serum samples were found to be seropositive. Brucellosis-related clinical symptoms were recorded in various seropositive cases. Animal contact, raw milk consumption, having an abortion history and the experience of an intrauterine fetal death were associated with seropositivity for brucellosis in univariate analyses (allp <0.05). In multiple logistic regression models only the contact with animals remained as independent and robust risk factor (odds ratio 5.21; 95 % CI: 1.88-13.75;p = 0.001) for seropositivity. Conclusion Brucellosis is a serious threat for pregnant women and their unborn children in Pakistan. Pregnant women having brucellosis-related symptoms or previous history of abortions, miscarriages, intrauterine fetal death and other brucellosis-related manifestations should be screened for brucellosis – especially those exposed to animals given the increased risk – and medication should be administered according to state of the art.